Applicability of Malaysian standards and universal design in public buildings in Putrajaya / Syazwani Abdul Kadir and Mariam Jamaludin. - Abdul Kadir, Syazwani; Jamaludin, Mariam (Universiti Teknologi MARA Cawangan Selangor, 2018)
This paper discusses an on-going research on universal design implementation in public buildings in Putrajaya with the applicability to Malaysian Standards of accessibility. The areas of study include disability and accessibility issues, current accessibility system in Malaysia, Malaysian Standards and universal design implementation in built environment, and the importance of public buildings in Putrajaya. Site observation involving facilities measurement and photographic documentation was conducted in ßve signißcant public buildings in this city. The ßndings of this study may be used as reference to designers and building managements in providing adequate accessible facilities for the buildings' visitors.